2018
DOI: 10.1039/c7en01029j
|View full text |Cite
|
Sign up to set email alerts
|

Cellulose nanomaterials: promising sustainable nanomaterials for application in water/wastewater treatment processes

Abstract: Schematic diagram showing the various water/wastewater treatment processes in which CN-based systems can be utilized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
116
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 211 publications
(119 citation statements)
references
References 147 publications
0
116
0
Order By: Relevance
“…The studies by Menezes-Silva et al [52] on the nanocrystalline cellulose obtained from eucalyptus pulp as an addition to glass-ionomer cements indicated an increase in the compressive strength in all considered samples in the range of 24.5-33.1% and in the case of flexural strength-by 19.9%-52.2% in relation to the control samples. Cao et al [18] observed an increase in flexural strength of the cement mortars modified with cellulose nanocrystals by 30% at 0.2% nanopolymer (v/v) in relation to the cement. The studies indicated that the hydration degree increased along with the CCNC content.…”
Section: Physical and Mechanical Properties Of Cement Mortarsmentioning
confidence: 99%
“…The studies by Menezes-Silva et al [52] on the nanocrystalline cellulose obtained from eucalyptus pulp as an addition to glass-ionomer cements indicated an increase in the compressive strength in all considered samples in the range of 24.5-33.1% and in the case of flexural strength-by 19.9%-52.2% in relation to the control samples. Cao et al [18] observed an increase in flexural strength of the cement mortars modified with cellulose nanocrystals by 30% at 0.2% nanopolymer (v/v) in relation to the cement. The studies indicated that the hydration degree increased along with the CCNC content.…”
Section: Physical and Mechanical Properties Of Cement Mortarsmentioning
confidence: 99%
“…The grafted moiety generated a higher surface area and hydrophilicity significantly favored removal of pharmaceutical chemicals by electrostatic interactions . In addition, utilization of nanocellulosic materials in other advanced water treatment technologies comprised of catalysts and disinfectants has been recently widely applied for remediation of industrial effluent and microorganisms . Several studies have presented nanocellulosic‐based materials as ideal and promising candidates toward their interesting activity as supports for the catalyst and disinfectants in water remediation.…”
Section: Nc As Bioadsorbents In Water Treatmentmentioning
confidence: 99%
“…In its dimeric form, the molecule is called “cellobiose” which represents the repeating units that make up the cellulose polymer chain [Figure (b)] . This structural build‐up empowers cellulose to possess several beneficial properties, such as high internal network assembly potential, biocompatibility, biodegradability, low cytotoxicity, chirality, and numerous modifiable hydroxyl groups . Naturally, cellulose is a semicrystalline polymer with fiber width range between 5–20 μm and 0.5 μm to several millimeters in length .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations